Influence of catchment characteristics on the relationship between land use and lake water quality in County Clare - Wemaëre, Alice (Trinity Centre for the Environment, 2005)
This research aims to identify the impacts of varying land use and physical environments on lake water quality based on an extensive study of sixty-nine catchments in County Clare, Ireland, combined with a more detailed study of a single catchment. Between March 2000 and October 2001, a comprehensive monitoring of sixty-nine lakes was carried out in County Clare, Data on catchment characteristics (topography, slope, soil characteristics, hydrology, forestry, agricultural land use and human activities) were compiled and spatially analysed using a Geographic Information System (GIS) Two main types of landscape were identified among the catchments. Calcareous catchments, with permeable carboniferous limestone bedrock, were associated with lower elevation and well/moderately-drained soils, such as brown earths, rendzinas and grey-brown podzolics, while acidic catchments had impermeable shale bedrock and poorly drained soils, such as peats and gleys. Calcareous catchments usually had greater drainage areas and were associated with lakes of greater surface areas, volumes and shorelines than acidic catchments. Land use distribution among the catchments reflected the influence of the physical environment, with greater coverage of pasture and broadleaf forests observed in calcareous catchments, while peatlands and coniferous forests were associated with acidic catchments.
Keywords: Environmental Science, Ph.D.; Ph.D. Trinity College Dublin